Multiplex-Heterogeneous Network-Based Capturing Potential SNP “Switches” of Pathways Associating With Diverse Disease Characteristics of Asthma - Ran, Ming-Yu; Yuan, Zhang; Fan, Chui-Ting; Ke, Zhou; Wang, Xin-Xing; Sun, Jia-Yuan; Su, Dong-Ju (Frontiers in Cell and Developmental Biology, 2021)
Asthma is a complex heterogeneous respiratory disorder. Nowadays, nubbly regions of the role of genetic variants and transcriptome including mRNAs, microRNAs and long non-coding RNAs in the pathogenesis of asthma have been separately excavated by massive independent studies. However, a comprehensive perspective of systematically integrating and decoding this scattered information, which can conduce to meticulously inspecting the internal communication of asthma, still remains a vacancy. To generate new insights into the pathogenesis of asthma, we ascertained three asthma characteristics according to reviews, i.e. airway inflammation, airway hyperresponsiveness and airway remodeling, and manually created a contemporary catalog of corresponding risk transcriptome including mRNAs, miRNAs and lncRNAs. A multiplex-heterogeneous networks-based approach called MIMP, measuring the relevance of disease characteristics to pathway by the similarity between the determined vectors of risk transcriptome and pathway in the same low-dimensional vector space, was developed for more concentrative and in-depth exploration of potential pathways. Then we integrated experimentally validated competing endogenous RNA regulatory information and the SNP in of marked significance pathway into ceRNA-mediated SNP switching pathway network (CSSPN) to intuitively analyze ceRNA regulation of pathways and the role of SNP in these functional dysregulations. Our study showed a systematic and propagable workflow of capturing the potential SNP 'switch' of asthma through text and database mining and might provide further information for the studies in pathogenesis of asthma.